Identification of influence factors for the implementation of communication curricula in dental education. (14th December 2017) - Rüttermann, S.; Kiessling, C.; Haak, R.; Gerhardt‐Szep, S.; Härtl, A.
Abstract: Introduction: The aim of the study was to reveal possible obstacles or advantages for the implementation of a dental communication curriculum. It was questioned whether (i) universities with a communication curriculum in medicine realise the same development in dentistry, (ii) the existence and usage of a learning objectives catalogue is a main factor to facilitate the implementation, and (iii) it is more easy to establish with a lower number of students. Material and methods: Data of two recently published surveys were taken as the basis for further analysis. The quality of the curricula was evaluated by a scoring system. Correlations were calculated between the scores and possible influence factors. A t test for paired samples was accomplished to reveal differences between medical and dental curricula, and a Mann‐Whitney U test to identify differences in schools with and without the usage of a learning objectives catalogue. Results: No significant correlation was found between the quality scores of medical and dental schools; t tests revealed significant differences between them ( P  = .004). Correlation between cohort size and quality of the curriculum was marginal. Mann‐Whitney U test revealed significantly higher quality scores for dental schools using a learning objectives catalogue ( P  = .001). Conclusions: The existence of a learning objectives catalogue might facilitate the implementation of communication curricula at dental schools. A missing notable curriculum in the corresponding medical school should not detain from a respective campaign in the dental curriculum. Large student numbers should also not discourage from developing a communication curriculum.